Comparative Study on Growth Characteristics and Early Selection Efficiency of Hybrid Offspring of Populus deltoides ‘DD-109’ and P. maximowiczii in Liaoning, China - Wei Liu; Chenggong Liu; Yan Zhang; Jinhua Li; Jiabao Ji; Xiaorui Qin; Fenfen Liu; Chengcheng Gao; Nairui Wang; Xueli Zhang; Ning Liu; Rusheng Peng; et al. (Plants)
Poplar is an important tree species for timber supply and ecological protection in northern China. Cultivating and selecting high-quality varieties and germplasm resources suitable for cultivation are key factors in enhancing the quality and productivity of poplar plantations in the arid and semi-arid northern regions with shorter growing seasons. This study conducted a field cultivation experiment on 10 progeny clones from the direct cross (D × M) of imported Populus deltoides ‘DD-109’ with Populus maximowiczii and 7 progeny clones from the reciprocal cross (M × D) using one-year-old rooted cuttings planted at a 4 m × 8 m spacing. Based on 17 years of annual growth observations, the study systematically compared growth characteristics, age of quantitative maturity, path relationships between traits, and early selection efficiency in the hybrid offspring. The results indicated that the D × M population had superior diameter at breast height (DBH), tree height (H), and volume (V) compared to the M × D population, while the height-to-diameter ratio (HDR) was lower. The growth rate of the 17 clones peaked from 10 to 14 years, with annual volume growth increments (PAIs) higher than mean annual volume increments (MAIs) during the early growth stages; the quantitative maturity age ranged between 12 and 16 years. The D × M population generally reached quantitative maturity earlier than the M × D population, with the fastest clone maturing in 12 years. Four clones (DM-9-17, DM-9-18, DM-9-14, and MD-61) showed values for V, DBH, H, and HDR above the hybrid group average. Path analysis demonstrated that DBH had the most significant direct and indirect effects on V, suggesting it as the best predictor for V. Using DBH as a reference, correlation and early selection efficiency analysis showed a strong relationship between growth characteristics at planting years 4–5 and later-stage performance, indicating this as the optimal period for early selection. These findings contribute to evaluating the production potential of P. deltoides ‘DD-109’ and P. maximowiczii germplasm in northern China and provide valuable guidance for selecting poplar clones suitable for local cultivation, accelerating breeding processes, and informing management planning for poplar plantations.